The Role of The Two Wheel Vehicle Patrol Unit Sabhara Unit in Preventing the Crime of Vehicle Theft During the Covid-19 Pandemic in the Jurisdiction of the South Tangerang Police - Andhira Andhira (Indonesian Journal of Police Studies, 2021)
This study was conducted to examine how the practice of patrolling 2-wheeled vehicles by the Sabhara Police Unit of South Tangerang in order to prevent the occurrence of the crime of motor vehicle theft. The reason for reviewing the research is that preventive measures are better than repressive measures or law enforcement. Motor vehicle theft is a prominent crime in South Tangerang City in 2018. The theories used in this research are management theory, crime prevention theory, communication theory, routine activity theory, police science and the concept of police patrol. The approach used in this study is a qualitative approach. A qualitative approach is used so that the author can explore related matters and also get a specific and real picture of the problems that caused 306 cases to be suppressed so that it decreased to 201 cases in 2019 and 278 cases in 2020. adopted in this study and the method used in this research is the case study method. The conclusion of this study is that the high number of cases of motor vehicle theft in the jurisdiction of the South Tangerang Police is influenced by several things, namely the number of incidents, the mode used by the perpetrators, and the last is the pattern of the place where the cases are committed by the perpetrators targeting housing/settlements carried out at odd hours. victim rest. The implementation of this dialogical patrol is very important to be carried out with the aim of creating communication between police officers and the community. The decline in the number of motor vehicle thefts in the following year compared to previous years, according to the evaluation by the South Tangerang Police, is a joint success of the South Tangerang Police and the community in preventing the crime of motor vehicle theft. Factors that affect dialogical patrol activities consist of external factors and internal factors. Suggestions in implementing dialogical patrol activities are the need for community participation efforts in crime prevention. There is a need for SOPs on dialogical patrol activities. Control over members of the leadership must always be carried out, so that in the implementation of activities there is no manipulation and activities can run optimally. Patrol members can also coordinate with bhabinkamtibmas in carrying out patrol activities involving residents in their area